The influence of oil sands development on trapping in the Fort McMurray region ... - Fox, M.; Ross, W. A. (University of Alberta Library, 1979)
A study of trapper demography, motivations, and trapping patterns was done in the area around Fort McMurray, Alberta for the Alberta Oil Sands Environmental Research Program. The objectives of the study were: (1) to establish baseline information;(2) to predict the future of trapping in the region; and (3) to propose a management survey that will lessen the negative effects of oil sands development on trappers. Data were collected from the trappers by the use of two interview schedules and winter trapline visits. Secondary data from the Alberta Fish and Wildlife Division were also used in the study. Interviews with Fish and Wildlife management and enforcement officials were tapped. Registered trappers were 70 percent native; the average age was 46. The majority held other jobs concurrently, and spent less than two months on the trapline in 1975-76 (a low year on the fur cycle). Several trapline variables were analyzed for their effect on trapping income. Trapper effort was found to be the most significant, ...